The Students’ Perception toward Dictogloss Technique Applied in their Writing Class - Moh. Choirul Huda (STKIP PGRI Tulungagung, 2022)
Writing has always been regarded as playing an important role in learning a foreign or second language. Hence, as an educator, it is important to always make an experiment or innovation to lead the students into success in their learning of writing. This study is focused on the revelation of students’ perception toward Dictogloss technique applied in the writing class. The research design is descriptive research with quantitative approach. The data were collected through a questionnaire administered to 20 students from the eleventh-grade students of MA Sunan Giri Gondang. The findings show that the average score of internal factors is 64,7 or 81%, it means that it has Very Good rating scale or it can be inferred as positive perception. Besides, the average score of external factor shows 68 or 85% which is categorized as Very Good rating scale, it means that the students’ perception from external factor can be inferred as positive perception as well. Furthermore, the data got from interview session shows that most of the students have good response to the technique. In other word, they have positive perception toward Dictogloss technique.